Multilingual individuals and multilingual societies (Hamburg studies on multilingualism, 2012)
The 25 contributions of this volume represent a selection from the more than 120 papers originally presented at the International Conference on "Multilingual Individuals and Multilingual Societies" (MIMS), held in Hamburg (October 2010) and organized by the Collaborative Research Center "Multilingualism" after twelve years of successful research. It presents a panorama of contemporary research in multilingualism covering three fields of investigation: (1) the simultaneous and successive acquisition of more than one language, including language attrition in multilingual settings, (2) historical aspects of multilingualism and variance, and (3) multilingual communication. The papers cover a vast variety of linguistic phenomena including morphology, syntax, segmental and prosodic phonology as well as discourse production and language use, taking both individual and societal aspects of multilingualism into account. The languages addressed include numerous Romance, Slavic and Germanic varieties as well as Welsh, Hungarian, Turkish, and several South African autochthonous languages